(3GdeDTQGJ GdeQLYjI dEfJbGA hJhLjg GdfTiA aj SHGbGJ GdfUa WhjdI aj CdYGH Gdbhi (B: (3OQGSI ejOGfjI dHYV hdGjGJ GdTQb GdLRGFQjs - (3Ydhj, efjQs; (3ejehfj, fHjdIs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2016)
(3gOaJ gPg GdOQGSI dGSJNdGU HYV GdeDTQGJ GdeQLYjI GdBJQhHheJQjI hGdajRjhdhLjI hGdHOfjI GdNGUI HaFI GdfGTFjf ef Sf (B12- 15 (3SfI MJi jJecf GdeOQHjf aj GdGYJeGO Ydi gPg GdeDTQGJ cSfO aj YedjI GdGfJbGA hGdJhLjg aj GNJUGUGJ GdfUa GdWhjdI GVGaI Edi GSJfHGW Sde Jbjjej jJe hab Jbjje GdWad aj GdbjGSGJ hGdGNJHGQGJ Ydi YOI eYGjjQ(B. s
(3GdOcJhQGgs
Keywords: (3GdEfJbGA h GdJhLjgs; (3GdJOQjH GdQjGVjs; (3GdSHGbGJs; (3CdYGH Gdbhis